Development of a Web-Based Diabetes Education Program for Health Care Professionals - OKUROĞLU, GÜLTEN; ALPAR, ŞULE (SLACK INC, 2016)
This study developed a Web-based type 2 diabetes education program (WB-DEP) for health care professionals. The methodology consisted of a pretest-posttest quasi-experimental approach. The study group consisted of 44 nurses and six midwives who volunteered for the study. The WB-DEP was developed in accordance with the effective teaching design model of Morrison, Ross, and Kemp. Data for the study were collected using the Information Form, The Section Evaluation Tests, the Web-Based Teaching Material Evaluation Scale, and the WB-DEP Opinion Form. In the statistical evaluation of the data, the averages, percentages, frequencies, and mean values were calculated, and the Wilcoxon signed-rank test was also used. According to the results, the study group believed that the WB-DEP was generally useful, successful, beneficial, informative, and understandable. In addition, the WB-DEP was found to significantly increase participants' knowledge about diabetes.